How to Allocate R&D (and Other) Subsidies: An Experimentally Tested Policy Recommendation - Thomas Giebe; Tim Grebe; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
This paper evaluates how R&D subsidies to the business sector are typically awarded. We identify two sources of ine_ciency: the selection based on a ranking of individual projects, rather than complete allocations, and the failure to induce competition among applicants in order to extract and use information about the necessary funding. In order to correct these ine_- ciencies we propose mechanisms that include some form of an auction in which applicants bid for subsidies. Our proposals are tested in a simulation and in controlled lab experiments. The results suggest that adopting our proposals may considerably improve the allocation.
urn:nbn:de:bvb:19-epub-13443-0
Keywords: D44; D45; H25; O32; O38; 330; Research; Subsidies; Experimental Economics